The effects of N-acetylcysteine on respiratory muscle fatigue during heavy exercise - Kelly, Megan K (Kansas State University, 2008)
Diaphragmatic fatigue is known to limit endurance performance during heavy exercise in humans. Previous reports have shown that diaphragmatic fatigue is reduced in rats with N-acetylcysteine (NAC; a nonspecific antioxidant) infusion, suggesting that oxidative stress contributes to this fatigue. However, it is not known if oral supplementation of NAC will reduce respiratory muscle fatigue during heavy exercise in humans. Therefore, the purpose of this study was to determine the effect of an acute oral dose of NAC on respiratory muscle fatigue during whole body heavy exercise. Eight healthy, non-smoking men (22+/-2 yrs), with no history of cardiovascular or lung disease, completed baseline pulmonary function tests followed by an incremental cycle VO[subscript 2peak] test. A randomized, double blind crossover design was then used where subjects were given either placebo (PLA) or NAC (1800 mg) 45 min prior to a 30 minute constant load (85% VO[subscript 2peak]) discontinuous (six-five minute stages) or continuous (cycle until volitional exhaustion) exercise test. Tests were separated by approximately one week. Maximum pressures (inspiratory, PImax; expiratory, PEmax) and venous blood samples (plasma lactate and total plasma glutathione) were made prior to- and following each 5-min of exercise in discontinuous tests and pre- and post-exercise in continuous tests. Subject's VO[subscript 2peak] was 43+/-5 ml/kg/min. There was no difference (p>0.05) in PImax between NAC (127.9+/-34.1 cmH[subscript2]O) or PLA (134.1+/-28.1 cmH2O) at rest. During exercise, PImax was significantly lower ([similar to]14%) in 6 of 8 subjects with PLA compared to NAC at minutes 25 and 30 of the discontinuous test indicating respiratory muscle fatigue. With NAC, PImax did not change (p>0.05) from rest throughout exercise indicating no respiratory muscle fatigue. There was no difference (p>0.05) in PEmax, plasma glutathione, lactate, oxygen uptake (VO[subscript 2]), ventilation (VE), heart rate (HR), or rating of perceived exertion between PLA and NAC at rest or during exercise. Time to exhaustion was not different (p>0.05) during the continuous tests (PLA: 1263 + 334 sec; NAC: 1047 + 136 sec). These results suggest that an acute dose of NAC reduces respiratory muscle fatigue during high intensity exercise but does not alter other ventilatory or metabolic indices. The significance of this reduced respiratory muscle fatigue with NAC on whole body exercise performance remains to be determined.
Keywords: respiratory muscles; antioxidants; exercise; Biology, Animal Physiology (0433)